Acute pancreatitis in pregnancy - from etiopathogenesis to therapy - Tesic Rajkovic, Snezana; Radovanovic Dinic, Biljana (Acta medicae Medianae, 2020)
Abstract: Acute pancreatitis (AP) in pregnancy is a relatively rare disease, but at the same time a great challenge for any physician, since it poses a potential threat to both the mother and the fetus. The occurrence of this serious disease requires multidisciplinary efforts in both the diagnosis and treatment, with the involvement of a gynecologists, gastroenterologists and surgeons. AP is more frequent in the third trimester and postpartal period. Pregnancy has long been considered as a possible cause of acute pancreatitis. However, more recent studies have shown that in pregnancy the main causes for the development of AP are gallstones or hyperlipidemia, accounting for a higher incidence of this disease in pregnant women. The diagnosis of acute pancreatitis in pregnancy can be a challenge for the clinician, since the clinical manifestations may resemble various pregnancy complications, such as hyperemesis gravidarum, placental abruption or ruptured ectopic pregnancy. Treatment strategy involves an assessment of both maternal and fetal risks. During severe AP, when there is single or multiple organ failure, emergency childbirth may be necessary. There have been no standardized recommendations for delivery for women with AP in their third trimester in order to reduce maternal and neonatal morbidity and mortality. Larger clinical studies are required for the formulation of recommendations for the diagnosis, follow-up of the clinical course and treatment of AP in pregnant women. Keywords: pancreatitis, pregnancy, diagnosis, therapy